Anatomic Variability of the Gall Bladder as Determined by the Advanced Imaging Techniques - E. V. Chaplygina; S. I. Klimova (Медицинский вестник Юга России, 2012)
Purpose: To study typical patterns of variability of the anatomical structure of the gall bladder.Materials and Methods: Somatotype of 310 adolescents of both sexes without pathology of the digestive system by the method of L. Rees, H.J. Eysenck, followed by ultrasound of the gallbladder. Sonography of the gallbladder was performed according to standard procedure.Results: It was established that the average values of all parameters studied in boys was significantly higher than that of girls.Summary: The size and shape of the gallbladderdepends on the physical type of the subject.